DISTANCE EDUCATION SYSTEM IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Traditional educational systems are now widely used in universities in Uzbekistan. The development of modern information technologies has also contributed to the development of distance learning in Uzbekistan. The Government has done a lot to promote distance education. In this article, we will review the system of distance learning in Uzbekistan.